Digital skills in tourism and hospitality as a precondition for the sector resilient growth: The case of Serbia - Lazić, Milena; Bradić-Martinović, Aleksandra; Banović, Jelena (Hotel and Tourism Management, 2023)
Advanced digital solutions, modern technologies and artificial intelligence have fundamentally transformed the pace of change and existing business models in the tourism and hospitality (T&H) sector. Implementing advanced digital solutions through new and improved tourism products and services can transform the customer experience while increasing the sector’s productivity and resilience. However, in order to adequately leverage advanced digital technologies, the T&H sector’s workforce must have a sufficient level of digital skills, competencies, and capabilities. Accordingly, this paper aims to assess the digital skills of the T&H sector employees in Serbia and identify the key factors that influence their level. The findings suggest that the digital skills of employees in the T&H sector in Serbia should be improved through formal and informal education in order for the sector to reposition itself in a more resilient and sustainable manner and in line with the 2030 Agenda.